Effect of Microfinance Institutions Activities on the Satisfaction of Women Entrepreneurs in Adamawa State, Nigeria - Fudamu, Aliyu Umaru (Kashere Journal of Politics and International Relations, 2023)
Women entrepreneurs in Adamawa State, like many others in the federation, are still slow to emerge, and the majority of these women entrepreneurs are unlikely to survive more than five years after their establishment. Also, the level of patronage of local businesses, especially those run by women within the state, is low compared to others due to the inability of these women entrepreneurs to present their products to a standard that can attract and satisfy customers. The main objective of this study is to examine the effect of microfinance institutions’ activities on the satisfaction of women entrepreneurs in Adamawa State. To elicit reliable and accurate information, a total of four hundred and two (402) women entrepreneurs were used randomly within Yola metropolis. A causal design was adopted for the study. The study used questionnaire as a tool for collecting data. The data collected for this study were subjected to descriptive analysis, such as frequencies and percentages that are presented in tabular form, and inferential statistics using multiple regression analysis with the help of Statistical Package for Social Sciences (SPSS) at 0.05 (5%) level of significance. The outcome of the study revealed that there is a significant effect of credit facilities, loan repayment plans, interest rates charged on loans, skill training, and supervisory roles on the satisfaction of women entrepreneurs in Adamawa State, Nigeria. Based on the findings, the study recommends that the management of the selected microfinance banks make credit facilities available and accessible to women entrepreneurs to meet customer taste and new customer needs.